Keinginan rasa cinta, kehormatan dan kemasyhuran dalam puisi terpilih Dharmawijaya / Mohd Fadzil Baharudin - Mohd Fadzil , Baharudin (2017)
The study reviewed selected poems by Dharmawijaya, Warna Maya (1974), Derita Buana (1992), Jejak Kembara (1999) and Mutiara Kenangan (2006). Freudian Psychoanalysis Theory was used to improve the understanding and appreciation of the literary works. Sigmund Freud (1899) was a psychologist who wrote about the desire for love, honour and fame. This study elaborated on the poet’s Dharmawijaya feeling, experience, desire and behaviour which inspired the writing of the poems. Problems in the study were analysed from the perspectives of oneself, the society and the environment surrounding the life of the poet. Qualitative textual analysis was performed taking into account the life and experience of Dharmawijaya. Library research as well as interviews were conducted to achieve the research objectives. Dharmawijaya’s poems were analysed to evaluate the entent of the poet’s intention and portrayal of love, honour and fame. The poet’s desire influenced his thoughts and creativity which were evidently seen via self, society and environment. The application of appropriate Freudian Psychoanalysis Theory such as the self-defence mechanism assisted the poet to deliver his desire based on his life experience. The poet expressed his life struggles through his poems. Research done on his poems proved that his life experience influenced his desire towards love, honour and fame. This study revealed that self-defense mechanism such as repression, sublimation and replacement played certain roles in expressing their desire vividly. The poet’s life struggles delineated his style. In summary, the poet‘s life experience has influenced his expression of desire for love, honour and fame through self-defense mechanism.